United Republic of Tanzania : First Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Macroeconomic developments remain favorable. Economic growth was strong during the first half of 2014 and is expected to remain close to 7 percent. Inflation remains in mid-single digits, consistent with the authorities' target of 5 percent by June 2015. New national accounts statistics show an upward revision of the 2007 GDP by 28 percent. The full series will be reflected in the program at the next review. Program performance through June was broadly satisfactory but has deteriorated since and risks have risen. While all end-June assessment criteria were met, most end-September indicative targets were missed. The continuous assessment criterion on non-accumulation of external arrears was also missed and structural reform implementation was slower than expected. These developments reflect a range of factors, including delays in donor financing related to governance concerns, delays in mobilizing external non-concessional borrowing (ENCB), revenue shortfalls, the authorities' decision to front-load domestically-financed capital expenditure, and coordination issues. Discussions focused on how to mitigate risks to budget implementation related to financing uncertainty and revenue shortfalls. Meeting the fiscal deficit target for 2014/15 will require revising downward revenue and expenditure during the mid-year budget review. Addressing forcefully and expeditiously the governance concerns arising from the IPTL case will be critical both for the resumption of donor financing and the business environment. In the meantime, the financing mix will tilt towards larger and more front-loaded ENCB. Better coordination of monetary and fiscal policies is required to reduce, and eventually eliminate, recourse to conversion of liquidity paper into financing paper. Government arrears will be addressed comprehensively. A plan to verify and clear existing suppliers' arrears (which continued to accumulate in 2013/14), better monitor, and prevent the emergence of new ones will be implemented in the coming year. Broad principles of a strategy to deal with arrears to pension funds have been agreed. Staff supports the authorities' request for the completion of the first PSI review, and proposes a waiver for non-observance of an assessment criterion and the modification of assessment criteria.